Energy saving in three-phase diode rectifiers using EI technique with adjustable switching frequency scheme - Davari, P.; Zare, Firuz; Yang, Y.; Kumar, D.; Blaabjerg, F. (2016)
© 2016 IEEE and EPE Association. A front-end rectifier can significantly impact a power electronics system performance and efficiency for applications such as motor drive where the system commonly operates under partial loading conditions. This paper proposes an adjustable switching frequency scheme using an electronic inductor technique to improve the energy saving of the system operating at partial loading. In the proposed solution, the switching frequency is adjusted based on the loading conditions, and thus maintains the system performance both in terms of switching losses and harmonic distortion. The obtained simulation and experimental results using the Si (Silicon) and SiC (Silicon Carbide) power devices confirm the effectiveness of the proposal. Furthermore, the impact of applied technique on conducted EMI (Electromagnetic Interference) performance of the system is also experimentally evaluated.